Looking Through Rainbow Coloured Glasses: Radio Spectral Variability and its Physical Origins - Ross, Kathryn (Curtin University, 2022)
This thesis investigates supermassive black holes in the centres of galaxies producing large, mushroom shaped clouds up to millions of light years across. We focus on baby black holes, which are smaller than typical radio galaxies, often just tens of thousands of light years across. Using telescopes around Australia, this work discovered these black holes are not as young as previously thought, but frustrated teens being restricted by a surrounding cloud of gas.